Challenges for sustaining local audio-visual ecosystems: Analysis of financing and production of domestic TV fiction in small media markets. Issue 1 (1st January 2016) - Raats, Tim; Evens, Tom; Ruelens, Sanne
Various trends, both technological and economic in nature, have led to a shift in the financing and production of serial television fiction (principally television drama and episodic comedy), resulting in pressure on existing financing of TV fiction. These pressures prove especially difficult for small nations and regions, being characterized by restricted markets, a limited number of active players, and barriers for export and scale. For media policy-makers, these transitions invoke a series of new challenges to sustain existing audio-visual ecosystems. Based on a case study of TV fiction in Flanders, and presenting evidence from a financial analysis of 46 TV fiction productions, this article analyses current financing streams, patterns and dynamics of TV fiction in small media markets. It seeks to reveal the composition of budgets and the relative importance of diverse agents and funders involved in TV fiction production. Critical evaluations are then offered as to whether current financing models and policy support mechanisms are fit to tackle the challenges posed by the increasing number of windows and increased fragmentation of TV fiction financing.